(untitled) (Belügyi Szemle, 2025)
Aim: The aim of this study is to explore the relationship between economic crime and cryptocurrencies, particularly with regard to the role that crypto assets can play in the commission of economic crimes and in removing illicitly obtained assets from the authorities' purview. The main hypothesis is that cryptocurrencies can be interpreted not only as a financial innovation, but also as a means of opening up new dimensions in the field of crime. Methodology: The analysis is based on qualitative research methods, drawing on the law enforcement experience of the prosecution office and the findings of a targeted investigation conducted by the Prosecutor General's Office into cryptocurrencies. Findings: The primary finding of the study is that the decentralized, pseudo-anonymous nature of cryptocurrencies can pose significant risks: it can facilitate the spread of economic crime and also affect the structure of economic crimes. The anonymity and easy access characteristic of cryptocurrencies hinder the effective action of law enforcement authorities in detecting and prosecuting perpetrators. Crypto assets are also suitable for withdrawing criminal proceeds from the authorities. Value: The study highlights that, thanks to technological advances and the spread of digitalization, economic criminals now have a wider range of tools at their disposal. White-collar criminals have no particular problem adapting to the changed global circumstances; in fact, they use them to their advantage when committing crimes. The prosecution's experience in applying the law and its investigation into cryptocurrencies can contribute to the development of law enforcement practices.